Помогите пожалуйста преобразовать в многочлен подчёркнутые выражения

0 голосов
19 просмотров

Помогите пожалуйста преобразовать в многочлен подчёркнутые выражения


image

Алгебра (93 баллов) | 19 просмотров
Дан 1 ответ
0 голосов

А)
2 {(a - b)}^{2} = 2( {a}^{2} - 2ab + {b}^{2} ) = 2 {a}^{2} - 4ab + 2 {b}^{2}
б)
a {(1 + 2a)}^{2} = a(1 + 4a + 4 {a}^{2} ) = a + 4 {a}^{2} + 4 {a}^{3}
в)
- 6(2x - y) ^{2} = - 6(4 {x}^{2} - 4xy + {y}^{2} ) = - 24 {x}^{2} + 24xy - 6 {y}^{2}
г)
- y {(3x - y)}^{2} = - y(9 {x}^{2} - 6 xy + {y}^{2} ) = - 9 {x}^{2} y + 6x {y}^{2} - {y}^{3}

(41.5k баллов)